Cyclocurcumin, a Minor Curcuminoid, Is a Novel Candidate for Hypopigmentary Skin Disorders with Melanogenesis-Stimulating Capacity - Shilpi Goenka (MDPI AG, 2024)
Effective therapies to treat skin hypopigmentation disorders caused by diminished melanin synthesis or export are limited due to potential side effects. In this work, we explored if cyclocurcumin (CYC), a curcuminoid found in minor amounts in turmeric rhizomes, might enhance the process of melanogenesis. CYC did not demonstrate antioxidant activity as evaluated by the DPPH assay. At noncytotoxic concentrations, CYC robustly enhanced melanin synthesis and melanin export in B16F10 mouse melanoma cells, which was correlated to increased cellular tyrosinase activity. The melanogenesis-stimulating efficacy of CYC was enhanced in B16F10 cocultures with HaCaT cells. Next, our results in MNT-1 human melanoma cells confirmed that CYC is a stimulator of both melanin synthesis and melanin export and acts by upregulating microphthalmia transcription factor (MITF) protein, although CYC did not alter tyrosinase protein or tyrosinase activity in MNT-1 cells. Moreover, the examination of CYC in MNT-1:HaCaT cocultures continued to show a more potent effect on stimulating melanin synthesis, as well as its export to recipient keratinocytes. Finally, CYC was shown to demonstrate a potent capacity to stimulate melanin production in primary human melanocytes from a Caucasian donor (HEMn-LP cells), although the effects on cellular tyrosinase activity were biphasic. Taken together, this is the first study to report the novel finding that CYC is a potent promelanogenic candidate that exhibits potential utility in the therapeutic management of skin disorders arising due to hypopigmentation in humans. Future studies that examine the molecular mechanisms and elucidate the promelanogenic efficacy of CYC in vivo are necessary.